2006
DOI: 10.1002/sia.2525
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of sputtering yields and damage in C60 SIMS depth profiling of model organic materials

Abstract: Sputter-depth profiles of model organic thin films on silicon using C 60 primary ions have been employed to measure sputtering yields and depth resolution parameters. We demonstrate that some materials (polylactide, Irganox 1010) have a constant and high sputtering yield, which varies linearly with the primary ion energy, whereas another material (Alq 3 ) has lower, fluence-dependent sputtering yields. Analysis of multi-layered organic thin films reveals that the depth resolution is a function of both primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
184
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(205 citation statements)
references
References 9 publications
21
184
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12] For example, it is possible to analyze multilayered structures used in the electronics/semiconductor industry, 6,13 as well as perform molecular specific depth profiles of cells and other biologically important systems. [13][14][15][16][17][18][19][20] The critical issue for quantitative interpretation of depth profiles is the interface width, a quantity that reflects how precisely one can measure a change in composition. The depth profiling experiments utilizing C 60 in which interface widths between similar materials such as two metals 11,12 or two Langmuir-Blodgett films 14,15 give values of 8.7 and ∼23 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] For example, it is possible to analyze multilayered structures used in the electronics/semiconductor industry, 6,13 as well as perform molecular specific depth profiles of cells and other biologically important systems. [13][14][15][16][17][18][19][20] The critical issue for quantitative interpretation of depth profiles is the interface width, a quantity that reflects how precisely one can measure a change in composition. The depth profiling experiments utilizing C 60 in which interface widths between similar materials such as two metals 11,12 or two Langmuir-Blodgett films 14,15 give values of 8.7 and ∼23 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have utilized 300-nm trehalose sugar films spin-cast onto Si substrates as such a platform [8,11]. Recently, Shard et al have reported on a different system consisting of organic delta layers and demonstrates the depth dependence of depth resolution [16]. Together with an analytical model, parameters such as depth resolution, sputtering yield, and the thickness of the altered layer at the surface were able to be estimated.…”
mentioning
confidence: 99%
“…The substrate ion, on the contrary, is absent until the polymer ion intensity starts to decrease. The decrease in the polymer ion intensity and the increase in the substrate ion intensity occur simultaneously, as is normally observed in the depth profiling of polymer thin films (Shard et al 2007). From the profile, the film thickness at the valleys was estimated to be about 290 nm.…”
Section: Brmentioning
confidence: 54%
“…The interface is usually defined as the midpoint of the intensity gradient of a representative substrate ion (Shard et al 2007, Green et al 2009). The intensity profiles of the Al 2 O 3 -, SiO 2 -, and C 2 -ions were used to define the interface when mica, silicon wafer, and HOPG, respectively, were used as the substrates.…”
Section: Brmentioning
confidence: 99%